Community perceptions, beliefs and acceptability of renewable energies projects: A systematic mapping study (2023)
Renewable energy projects are being developed and implemented in different geographical areas of several continents. In each of them, many communities develop their lives that have cultural, social and environmental potentials; as well as perceptions, beliefs and criteria for the acceptance of renewable energy projects in their territories. Through the methodology of mapping SCOPUS articles published worldwide, this work examines the perceptions, beliefs and criteria of community acceptability against renewable energy projects that are based on the use of natural resources such as sun, water, wind, earth, and biomass. These perceptions and beliefs can come from ancestral traditions that mark the relationship of communities with beings of nature and not with natural resources, which is the modern vision. Other perceptions, beliefs and criteria of acceptability in non-ancestral communities may be related to risk perception, low levels of trust and credibility between stakeholders, confusion regarding the operation of renewable energy systems, among others. Whatever their origin, the experience in implementing these projects has taught about the relevance of involving communities during the stages of their development, the need to know the different places from where their worlds are explained and thus improving the levels of relevance, acceptance, and sustainability of renewable energy systems. © 2020, © 2020 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.